In vitro parameters of cryopreserved leucodepleted and non-leucodepleted red blood cells collected by apheresis or from whole blood and stored in AS-3 for 21 days after thawing - Bohoněk, Miloš; Petráš, Marek; Turek, Ivo; Urbanová, Jaroslava; Hrádek, Tomáš; Staropražská, Věra; Koštířová, Jitka; Horčičková, Dana; Duchková, Simona (Blood transfusion, 2014)
BACKGROUND: The aim of the study was to evaluate the in vitro quality of cryopreserved red blood cells obtained from different sources with or without leucodepletion and stored at 4±2 °C in AS-3 for up to 21 days. MATERIALS AND METHODS: Red blood cells were collected by four methods: double erythrocytapheresis, whole blood collection with buffy coat removal, double erythrocytapheresis with in-line leucofiltration, or whole blood collection with in-line leucofiltration. All four types of red blood cells were frozen in 40% glycerol after collection and stored at a temperature below -65 °C for at least 30 days, thawed, deglycerolised and subsequently reconstituted in AS-3. The in vitro haematological and biochemical properties of the thawed red blood cells were tested on days 0, 7, 14, and 21 after deglycerolisation and reconstitution. RESULTS: Overall, 72 units were processed. Leucodepletion of cryopreserved red blood cells units reduced haemolysis, lowered ammonia concentration, preserved pH and osmolality and led to sustained higher concentrations of ATP. In contrast, the source of red blood cells (apheresis or whole blood) did not affect their quality. DISCUSSION: The quality of all investigated red blood cells units was the same as or even better than that of erythrocytes obtained from double erythrocytapheresis with a 24-hour survival of at least 86% after up to 3 weeks of storage in AS-3.
Keywords: konzervace krve; Cytapheresis; Hemoglobins; techniky in vitro; Blood Preservation; Ammonia; Humans; kryoprezervace; erytrocyty; osmolární koncentrace; leukoredukce; Cryopreservation; Hydrogen-Ion Concentration; Leukocyte Reduction Procedures; Cryoprotective Agents; Adenosine Triphosphate; Glycerol; amoniak; koncentrace vodíkových iontů; Hemolysis; hemolýza; adenosintrifosfát; hemoglobiny; lidé; Erythrocytes; glycerol; Osmolar Concentration; cytaferéza; In Vitro Techniques; kryoprotektivní látky